Tell me about this, Bawoo! edutainment for the curious Filipino-Korean child designing a social media campaign that explores character design to encourage Filipino-Korean damunhwa children aged 9 to 12 to interact with Philippine culture - Youn, Gabrielle Natividad A.
Filipino-Korean damunhwa, or multicultural, children who are born in South Korea grow up surrounded by their Korean communities, and thus strongly identify with Korean culture. However, due to the limitations of the current damunhwa education in Korea, Filipino-Korean children have limited opportunities to learn about their Philippine heritage. Moreover, analysis of South Korean media shows that the image of the Philippines in South Korean media has not been positive. This could be detrimental, as Filipino-Korean children already lack exposure to Philippine culture. Currently, damunhwa education in South Korea focuses on integrating damunhwa people into Korean society, and lacks effort in encouraging the formation of a collective identity among damunhwa children.